Unknown Man Autobiography by a failure in almost everything except living life to the fullest... - Carroll, William (Raton, New Mexico Coda Publications, 2009)
A most unusual book: Autobiography by a failure in almost everything except living life to the fullest. For, as readers soon learn, he is somewhat unique for his massive collection of monumental mistakes. Though now and then he finds a success most surprising to him. For all that as it may be, Carroll has had a wonderful life and continues proud of his few abilities and the many supportive friends who have enhanced his way. From the last page of the book. "A few months after my return, while I was wandering down 2nd Street in Raton, one of the city's quietly prominent businessmen stopped me. With no preamble or greeting, he said "Tell me, Bill, just who are you? We can't find out anything about you." (The Unknown Man)
93321
Keywords: William Carroll; Autobiography